A preliminary study of human computer interaction (HCI) in IPTA’s and IT industries in Malaysia / Khazira Kasim Hawari - Hawari, Khazira Kasim (2010)
Human Computer Interaction (HCI) has becoming more and more important in developing new product in the market. Undergraduate learn HCI as part of their taught courses. IT industries implement HCI mainly in the area of developing and designing new product that their company is producing. As the expert in HCI is needed in designing the new product. The impact of HCI in the working environment, the benefit of the student who learn HCI and what kind of career they have with the knowledge and skills as someone who have HCI knowledge